Navigating the digital realm: the learning experiences of adolescents with autism spectrum disorder in online communication / Jasmine Jain and Koh Kian Seng - Jain, Jasmine; Koh, Kian Seng (Universiti Teknologi MARA, 2024)
Social communication is essential in the development of human relations, the core of one’s psychosocial well-being. Unfortunately, it is also one of the most significantly impaired aspects of people with Autistic Spectrum Disorder (ASD). For people with ASD to be independent and blend into society, they must learn some important life skills. However, it is extremely difficult for them to learn these life skills as they have an impairment of social communication, which plays a significant role in learning these skills based on some of the dominant learning theories. This research aims to explore and understand the online learning experiences of high-functioning adolescents with ASD through online synchronous and asynchronous communication. This study was conducted using a basic qualitative study based on the philosophy of basic and interpretive qualitative research. The research questions focused on the experiences of online learning through online communication among high-functioning adolescents with ASD and how they perceive the differences in the use of online synchronous and asynchronous communication during online learning. Eight participants were recruited through purposive and snowball sampling techniques. Data were collected through three sessions of semistructured interviews prioritised by data saturation instead of the number of recruited participants. The practice of reflexivity, along with member checking, and investigator triangulation were included to enhance a clear understanding of the data collection and analysis process which could persuade readers on the trustworthiness and validity of the study. The findings revealed six themes – ability to selfexpress, ability to understand others, sense of physical presence, feelings of warmth, useful software features, and effects of negative past experiences. The researcher provided several recommendations for future studies to enhance the quality of support provided to high-functioning adolescents with ASD during their transition to adulthood. This study sets a solid foundation for future studies to build upon and highlights the limited number of studies focused on high-functioning adolescents with ASD, especially regarding their online learning experiences via online synchronous and asynchronous communication.